Tumour growth model of cancer self-remission with hassell-varley functional response - Tang, Chiew Sim (2018)
Predator-prey like models with functional responses such as Holling type I and II have been studied previously to model the interaction between tumour cells, hunting predator cells and resting predator cells. The aim of this study is to introduce another type of functional response which is Hassell-Varley into predator-prey interaction of tumour model of cancer self-remission. Dimensional analysis, stability analysis and bifurcation analysis are used to analyse the model. Under certain condition, our numerical analysis showed an existence of Hopf-bifurcation for some parameter ranges, which generate periodic solution.